‘From Libya all of the Mediterranean coast is in its power’: the Roman expansion in Africa according to Strabo’s ‘Geography’ - Matias Ribeiro, Alaide (Romanitas - Revista de Estudos Grecolatinos, 2025)
In this article, the objective is to analyze how the Greek geographer Strabo of Amasia (64 BCE–24 CE) enunciated the process of Rome’s territorial expansion in North Africa. To do this, we will examine Book XVII of Geography, which contains the description of Libya. The relations established between Romans and Libyan peoples were marked by collaboration and conflict. Strabo, throughout his discourse, refers to Rome and the actions of its agents in the oikoumene, understanding Roman expansion in Libya as a process that began in the Republican period and was still ongoing in his time. It is concluded that the expansion is evidenced by terminology, exploitation of local resources, institution of provinces, and the presence of agents serving Rome in North African territory.